PERAN ISTERI DALAM MENJAGA STABILITAS EKONOMI KELUARGA NELAYAN - Usman Usman (LIPI Press, 2013)
The article aims to explain the role of wives in maintaining economic stability of fishermen family. The role of wives is not only limited in domestic domain, but also in the field of economic and social. For fishermen’s wives, gender bias which used to preserve the role of man and woman is not really dominant right now. In contrast, the wife has a greater and more dominant role in her family life. Furthermore, the wife is demanded to be more creative to cope with the fluctuative income of her husband. In consequence, it is not easy to be a wife of fisherman. There are three obligations should be done by the wife. Firstly, is the domestic duties; second, is being creative to assist the income of the husband; the last is participating in various social activities. Keywords: The role of wives, economic stability, fishermen